Affective computing in automotive industry - Mohd Hafiz, Mohd Hassin (Faculty of Computer System & Software Engineering, 2011)
Current state of the art in computer science is an attempt to build a system that understands us. Affective computing is one of the attempts made to build an information system that can detect, classify, and respond to human emotion. Affective computing is a combination of artificial intelligence and cognitive science that inspired researcher to build a computer system or robot that similar to “Commander Data” in Star Trek fiction movie. This article discusses the general architecture and applications of affective computing.